2020
DOI: 10.7150/ijms.42078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Artificial Intelligence in Kidney Disease

Abstract: Artificial intelligence (AI), as an advanced science technology, has been widely used in medical fields to promote medical development, mainly applied to early detections, disease diagnoses, and management. Owing to the huge number of patients, kidney disease remains a global health problem. Challenges remain in its diagnosis and treatment. AI could take individual conditions into account, produce suitable decisions and promise to make great strides in kidney disease management. Here, we review the current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 105 publications
0
31
0
Order By: Relevance
“…With the increasing sophistication of artificial intelligence, deep learning has been increasingly applied in various fields, including medicine [ 25 ]. The use of artificial intelligence for management of kidney disease has been recently proposed, and its potential has been well recognized by physicians [ 13 ]. Kuo et al [ 26 ] developed a deep learning model for predicting renal function by using kidney ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing sophistication of artificial intelligence, deep learning has been increasingly applied in various fields, including medicine [ 25 ]. The use of artificial intelligence for management of kidney disease has been recently proposed, and its potential has been well recognized by physicians [ 13 ]. Kuo et al [ 26 ] developed a deep learning model for predicting renal function by using kidney ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have recommended applying artificial intelligence to the management and prevention of kidney disease [ 13 ]. However, few studies have developed deep learning–based methods for detecting early renal function impairment from retinal images.…”
Section: Introductionmentioning
confidence: 99%
“…The interest is increasing rapidly in the application of risk score systems and artificial intelligence (AI)-based decision tree assisted technologies to monitor the patient safety [ 14 , 15 ]. In recent years, the accessibility of electronic medical records for big data in the healthcare and development of machine learning to AI has grown tremendously.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, a recent study integrates age, GDF15 biomarker, and clinical parameters as the ABC death risk score for clinical evaluation of patient safety and decision tree [ 12 ]. There has been increasing interest in identifying the novel death risk score model to effectively predict poor prognosis in CKD patients [ 13 , 14 , 15 ]. Emerging evidence has shown that the prognostic questionnaires of mortality in CKD and specifically in MHD patients serve as useful risk prediction tools for the early detection of clinical events.…”
Section: Introductionmentioning
confidence: 99%
“…The rise of machine learning is driven by the ability to process “big data” and the need to deliver the best possible value- and evidence-based care. The utility of artificial intelligence (AI) coupled with machine learning, has generated much interest and many studies in clinical medicine [ 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The machine learning approach has been developed recently for advantages in performance and extensibility and has become indispensable for solving complex problems in most sciences [ 80 , 81 , 82 ].…”
Section: Predicting Csa-aki By Machine Learningmentioning
confidence: 99%